Mapping information landscapes: new methods for exploring the development and teaching of information literacy - Whitworth, Andrew (Cambridge EBA Collection, 2020)
This is the first book to study how the political content of information literacy arises from the way it has become defined and is taught. It introduces new methods for research into the development of IL in learners and explores the implications of this research for the design of IL teaching, both in formal educational settings and in workplaces.